Milly-Molly-Mandy stories - Brisley, Joyce Lankester, 1896- (New York : D. McKay Co., 1976)
Thirteen adventures with Millicent Margaret Amanda including those in which she spends a penny, goes blackberrying, and makes a cosy.
Keywords: Country life -- England -- Fiction; Family life -- England -- Fiction; England -- Fiction